Strongly C-Compactness - Nasir, Ahmed Ibrahem (Al-Nahrain Journal of Science, 2018)
In this paper, we define another type of compactness which is called "strongly c-compactness ". Also, we study some properties of this type of compactness and the relationships with compactness, strongly compactness and c-compactness.